Combination of Tramadol-Paracetamol in Palliative Care Pain Management: A Case Report - Riris Sifa Fauziah (Faculty of Medicine, Universitas Airlangga, 2021)
One of the basic goals of palliative care is to reduce the suffering of the patient, which includes relieving the pain. Some facts show that sometimes a doctor is afraid to give opioid analgesic mono-therapy to his patients because she is worried on one hand about the effect of addiction. In addition, in some cases, NSAID analgesics mono-therapy can also cause a series of side effects or even the patient may be contraindicated against the use of NSAID or paracetamol class drugs. Actually, this can be prevented by giving a combination of opioids and non-opioids analgesic. By providing this combination of therapy, it is hoped that this can accelerate the onset of work, extend the working period which can reduce the dose of drugs consumed, and more importantly minimize the side effects of each drug. The fixed dose combination of Tramadol-Paracetamol (Tramadol 37.5 mg–Paracetamol 325 mg) is an example of a drug combination preparation that has been shown to be effective in the treatment of pain. In this case report, a patient who is currently undergoing palliative therapy for cancer is described. On the way, the patient felt spinal pain as a result of the spread of the disease. The combination of Tramadol-paracetamol was administered twice a day with a dose that adjusted to the VAS Score observations before and after drug administration. And in this case, there was a decrease in the VAS score after being given Tramadol-Paracetamol combination.